2022
DOI: 10.1021/acscatal.2c02953
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nonzeolite-Catalyzed Formation of Formaldehyde on the Methanol-to-Hydrocarbons Conversion

Abstract: Formaldehyde is an important intermediate that affects the catalyst performance in the methanol-to-hydrocarbons (MTH) conversion. In this study, photoelectron photoion coincidence spectroscopy was applied to elucidate the formation of this species in empty quartz and stainless steel reactors as well as over zeolite catalysts (ZSM-5 and BETA) and commonly used bed diluents (silicon carbide and quartz). The yields of formaldehyde in an empty stainless steel reactor and over the crude silicon carbide particles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…For example, we detected formaldehyde ( m / z = 30, Figure a,b), one of deactivating species formed from methanol disproportionation, which is difficult to detect with GC analysis. ,, A much stronger signal of formaldehyde was observed for HZSM-5 in comparison to Ca/ZSM-5. The lower production of formaldehyde, likely caused either by its decomposition over Ca cations or the lower Brønsted acidity of Ca/ZSM-5, can explain the slower deactivation observed for Ca/ZSM-5. , Similar results, showing suppressed formaldehyde production over Ca-modified zeolites, were reported by Paunović et al For ms-TPES with m / z 42, lack of signal at 9.6 eV shows that the yield of ketene is negligible with respect to that of propylene for both HZSM-5 and Ca/ZSM-5. At the same time, we observed more acetone ( m / z = 58), over Ca/ZSM-5.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…For example, we detected formaldehyde ( m / z = 30, Figure a,b), one of deactivating species formed from methanol disproportionation, which is difficult to detect with GC analysis. ,, A much stronger signal of formaldehyde was observed for HZSM-5 in comparison to Ca/ZSM-5. The lower production of formaldehyde, likely caused either by its decomposition over Ca cations or the lower Brønsted acidity of Ca/ZSM-5, can explain the slower deactivation observed for Ca/ZSM-5. , Similar results, showing suppressed formaldehyde production over Ca-modified zeolites, were reported by Paunović et al For ms-TPES with m / z 42, lack of signal at 9.6 eV shows that the yield of ketene is negligible with respect to that of propylene for both HZSM-5 and Ca/ZSM-5. At the same time, we observed more acetone ( m / z = 58), over Ca/ZSM-5.…”
Section: Resultssupporting
confidence: 80%
“…The lower production of formaldehyde, likely caused either by its decomposition over Ca cations or the lower Brønsted acidity of Ca/ZSM-5, can explain the slower deactivation observed for Ca/ZSM-5. 39,40 Similar results, showing suppressed formaldehyde production over Ca-modified zeolites, were reported by Paunovićet al 41 For ms-TPES with m/z 42, lack of signal at 9.6 eV shows that the yield of ketene is negligible with respect to that of propylene for both HZSM-5 and Ca/ZSM-5. At the same time, we observed more acetone (m/z = 58), over Ca/ ZSM-5.…”
Section: ■ Experimental Methodssupporting
confidence: 83%
“… In addition, formaldehyde is responsible for catalyst deactivation but can also increase the selectivity toward aromatics. PEPICO detection of this reactive species is currently also of great interest in the MTO community. , …”
Section: Applicationsmentioning
confidence: 99%
“…Along with formaldehyde, these so-called MIHT reactions produce methane and water, and more saturated hydrocarbons (e.g., alkanes). Recently, we showed that formaldehyde can also arise from methanol dehydrogenation over transition metal sites that may be present in the reactor walls and the bed-diluents . Formaldehyde is proposed to react with alkenes via Prins and hydroacylation reactions yielding dienes and polyenes, which readily undergo cyclization and HT, eventually yielding arenes. ,,,,,, Besides, formaldehyde can directly convert arenes into deactivating species, such as diphenylmethane .…”
Section: Introductionmentioning
confidence: 99%
“…They are also suspected to be the central promotors of the arene cycle and associated pathways that cause the formation of coke. ,,, However, the contribution of the FMRs to the deactivation of the catalysts exhibiting different acid properties under different reaction conditions is still elusive. This is to a significant extent caused by the challenging detection of this intermediate by conventional mass spectrometry and gas-chromatography techniques. , …”
Section: Introductionmentioning
confidence: 99%